Spermatozoa Viability of Filial Ettawa Goat After Sexing Process - Kusumawati, Enik Dwi; Leondro, Henny; Susilawati, Trinil; Isnaini, Nurul (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The use of albumin derived from egg white is a method that is easy to apply, cheap, effective for sexing semen process of separating the spermatozoa X and Y. The viability of Filial Ettawa goatspermatozoa after the sexing process using different percentages of albumin density egg white withcoconut water diluent and egg yolk diluents was examined. The egg white albumin densitytreatments were 3 gradients of 10%, 30% and 50%. Laboratory experiments were performed sexingspermatozoa using the 3 density gradients of egg white albumin with coconut water diluent and eggyolks diluents with a 20 minute incubation time. Each treatment was replicated 10 times. Data wasstatistically analyzed using analysis of variance model (ANOVA). The addition of coconut waterdiluent and egg yolk diluent provide a highly significant difference (p<0.01) in the spermatozoaseparation of the top and bottom layers, but the average value there is no significant difference. Thespermatozoa viability after sperm sexing found that using density gradient egg whites showed betterresults using egg yolk diluent compared to coconut water diluent. The top layer had a mean percentlive sperm of 78.52 ± 8.65% and the bottom layer had mean percent live sperm of 80.29 ± 8.735%.Further research is needed into the  quality of spermatozoa sexing results using varying gradients ofegg whites.Key Words: Sexing, Egg White Albumin Density, Diluent, Egg Yolk, Goat